2002
DOI: 10.1023/a:1014585522084
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The competent physician pursues lifelong learning through the recognition of deficiencies and the formulation of appropriate learning goals. Despite the accepted theoretical value of self-assessment, studies have consistently shown that the accuracy of self-assessment is poor. This paper examines the methodological issues that plague the measurement of self-assessment ability and presents several strategies that address these methodological problems within the current paradigm. In addition, the article propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(80 citation statements)
references
References 75 publications
1
72
0
7
Order By: Relevance
“…We excluded papers measuring Kirkpatrick Levels 1 and 2 outcomes because they focus simply on learner reactions and learning measured in a simulated environment. In addition, given the abundant literature on self-assessment inaccuracy,17,18 papers reporting solely self-assessment data and considered a Level 1 (reaction) outcome, were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded papers measuring Kirkpatrick Levels 1 and 2 outcomes because they focus simply on learner reactions and learning measured in a simulated environment. In addition, given the abundant literature on self-assessment inaccuracy,17,18 papers reporting solely self-assessment data and considered a Level 1 (reaction) outcome, were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, we consider that Bscoring accuracy^(the degree of closeness from the SSA scoring to an external source) needs to be differentiated from Bcontent accuracy.^While the vast majority of SSA accuracy research has focused on the first (e.g., Brown and Harris 2013), there is a need to study the latter which is, in our point of view and that of others (Ward et al 2002), of greater importance. We recommend that while simple studies of Bscoring accuracym ay be needed in some teaching contexts, there is a greater need to explore the interaction of SSA with variables that impact scoring accuracy.…”
Section: Factors Associated With Increased Accuracy In Ssamentioning
confidence: 99%
“…While it can be argued that there is no objective truth to be used as a yardstick against which self-assessment could be measured (see for a discussion on this topic Tan 2012b; Ward et al 2002), it is socially agreed, at least in education, that the realism of a self-assessment can be determined by the alignment of that self-judgment with performance on an externally administered test or task or against the judgments of appropriate content experts, such as teachers or even peers (Topping 2003). As an example of validating student perceptions with tested performance, consider research into memory of learning, known as BJudgment Of Learning^(JOL) (Nelson and Dunlosky 1991;Dunlosky and Nelson 1994;Meeter and Nelson 2003;Thiede and Dunlosky 1999).…”
Section: Implications For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of studies have concluded that a learner’s ability to self-assess accurately is quite poor. 15 Eva and Regehr 16 defuse this SDL paradox by recognizing that such fundamental skills required of SDL are not an inherently stable characteristic. Instead, one’s ability to self-assess is contextually bound and requires ongoing monitoring and incorporation of expert external evaluation to promote intrinsic SDL skills.…”
Section: Discussionmentioning
confidence: 99%